Pemberian Suntik Vitamin pada Hewan Ternak Sapi di Desa Mareje Kabupaten Lombok Barat - Lalu Bahrul Alam; Safnowandi Safnowandi; I Wayan Karmana (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aimed to improve the health and productivity of cattle while enhancing farmers’ knowledge regarding proper vitamin administration techniques. The activity involved several farmers through stages including identification of cattle requiring vitamins, initial health examination, administration of vitamin injections according to standard dosages, and post-injection observation. The results indicated that some cattle exhibited symptoms of vitamin deficiency, such as decreased appetite, slow growth, and poor physical condition. A total of 10 cattle were successfully injected with vitamins by the service team, which consisted of experts and trained students, with active participation from the farmers during the demonstration process. Post-injection observations showed that all cattle remained stable without adverse reactions, and within a few days, increased activity and improved physical condition were noted in previously weak animals. These findings suggest that vitamin administration via injection is more effective in improving cattle health compared to feed supplementation and successfully enhanced farmers’ knowledge and skills. The results underscore the importance of routine mentoring and the implementation of sustainable programs to maintain cattle health and increase farmers’ productivity.